Analysis of electromagnetic properties of Ce-Zn substituted barium hexaferrite for electronic circuit applications - Okutan, M.; Ozturk, M.; Kirsoy, A.; Araz, I; Yener, T.; Yalcin, O. (ELSEVIER, 2022)
Electromagnetic properties of Ce-Zn substituted barium hexaferrite (Ba0.5Ce0.5ZnFe11O19 ferrite) synthesized using ceramic technique were analyzed in detail in the X band frequencies to describe its response to microwave absorber and microwave electronic device applications. The phase formations, structural morphology, polarization mechanisms and magnetic properties for Ba0.5Ce0.5ZnFe11O19 ferrite, which provide important information about electrical load transmission mechanism were analyzed using X-ray diffraction, scanning electron microscopy, two-port vector network analyser and vibrating sample magnetometer techniques, respectively. The experimental complex dielectric plane plots (Cole-Cole plots) of the Ba0.5Ce0.5ZnFe11O19 ferrite represent an equivalent RC circuit corresponding to the impedance circuit in the Smith Chart. The reflection loss increased to the highest value (-17.04 dB) depending on the amount of Ce in the structure of the Ba0.5Ce0.5ZnFe11O19 ferrite and the bandwidth, which is important for microwave absorbers, increases.
Keywords: Electromagnetic properties; Permittivity; Permeability; Cole-cole plots; Equivalent circuit; Smith chart; MICROWAVE-ABSORPTION PROPERTIES; MAGNETIC-PROPERTIES; DIELECTRIC-PROPERTIES; FREQUENCY; BAFE12O19; FERRITES; BEHAVIOR; GRAIN; Physics